Using Modern Technologies in the Lesson - Xamid Soatovich, Raimov; Elmurod Egamberdievich, Rajabov; Yorqinoy Mahmudalievna, Nazarmatova; Nargiza Urolovna, Hakimova; Dildor Egamberdievna, Geldieva; Kizlarkhon Abduholiqqizi, Sharipova (International Journal of Psychosocial Rehabilitation, 2020)
The article deals with the new modern technologies in the lesson. Today we are living in the technology century. We can not imagine our lives without computers and the internet.